Development of TPACK-Oriented Learning Media For Game-Based Short-Distance Running Materials - Wirayudha, I Made Agus; Wijaya, Made Agus; Spynawati, Ni Luh Putu (JURNAL PENJAKORA, 2025)
This research aims to develop TPACK-oriented learning media for short distance running material for grade VII junior high school students. This development research uses the ADDIE model which consists of the Analyze, Design, Development, Implementation and Evaluation stages. This research instrument is in the form of product validation sheets from learning material experts, design experts and PE practitioners, as well as Formative Class Evaluation/FCE. The data analysis techniques used are descriptive-quantitative. Based on the results of the data analysis of the content/material expert instrument on the learning video, it was obtained that in the content expert test with a score of 93% in the very good category, the results of the data analysis of the design/media expert instrument on the learning video obtained a score of 95% in the very good category, while the results of the data analysis of the PE practitioner instrument got a score of 95% in the very good category. At the implementation stage, a small group test was carried out with a score of 2.97 From a maximum score of 3.00 it is classified as very good. Furthermore, at the evaluation stage, it can be stated that this learning media product in the form of video tutorials and motion tasks is suitable for use and can facilitate junior high school grade VII students to learn short-distance running material.